Launching Fuel Oil According to The Perspective of Positive Law and Sharia Economy (Study of Pelangsir in Palangka Raya City) - Zaenal Abidin; Khusnul Mufidati; Khairunnisa Khairunnisa; Abu Bakar; Muslimah Muslimah (Cahaya Abadi Publisher, 2022)
Fuel oil is currently the main need of the community in supporting various activities to drive the economy. Starting from providing electrical resources at home, motorized vehicles, and to trade as a source of income. To ease the burden on society and increase the wheels of the economy, the Government made a policy by providing subsidies for fuel. So that the price of fuel is not too high and affordable for the community. However, subsidized fuel is prone to misuse and even frequent irregularities, one of which is the practice of shifting. Shifting or known as ‘Melangsir” to the people of Palangkaraya city means buying subsidized fuel at gas stations and selling it at retail. This is qualitative research in which research data is obtained through observation, interviews, and documentation with suppliers or retailers, consumers. Furthermore, the data that has been collected is analyzed using descriptive analysis method. From the results of this study, it is explained that, according to the positive law regulated by Oil and Gas Law of Indonesian Law number 22 of 2001, Melangsir and buying and selling of retail fuel in Palangkaraya is a criminal act that is prohibited by the government, this is stated in Article 53. In Islamic Economic Practice shifting and buying and selling of retail fuel is permitted as long as it applies Islamic economic principles and aims for the benefit of all parties.